2014
DOI: 10.1371/journal.pone.0100383
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Responses to Organophosphate Substrate Additions in Contaminated Subsurface Sediments

Abstract: BackgroundRadionuclide- and heavy metal-contaminated subsurface sediments remain a legacy of Cold War nuclear weapons research and recent nuclear power plant failures. Within such contaminated sediments, remediation activities are necessary to mitigate groundwater contamination. A promising approach makes use of extant microbial communities capable of hydrolyzing organophosphate substrates to promote mineralization of soluble contaminants within deep subsurface environments.Methodology/Principal FindingsUraniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…Moreover, Yamada and Sekiguchi (2009) report that Anaerolineae can decompose carbohydrates, especially relatively recalcitrant carbon compounds; therefore, an increase in Anaerolineae would positively influence carbon cycling and promote nutrient release from organic compounds in soils. Similarly, Cao et al (2015) reported that AMF increase the abundance of Flavobacteriaceae, subsequently enhancing the availability and utilization of phosphorus in soils (Martinez et al, 2014). Therefore, it should be emphasized that AMF have positive effects not only on plants but also on soil microorganisms and soil function under ENP treatments.…”
Section: Amf Alleviate the Negative Influences Of Fe 3 O 4 Nps On Thementioning
confidence: 93%
“…Moreover, Yamada and Sekiguchi (2009) report that Anaerolineae can decompose carbohydrates, especially relatively recalcitrant carbon compounds; therefore, an increase in Anaerolineae would positively influence carbon cycling and promote nutrient release from organic compounds in soils. Similarly, Cao et al (2015) reported that AMF increase the abundance of Flavobacteriaceae, subsequently enhancing the availability and utilization of phosphorus in soils (Martinez et al, 2014). Therefore, it should be emphasized that AMF have positive effects not only on plants but also on soil microorganisms and soil function under ENP treatments.…”
Section: Amf Alleviate the Negative Influences Of Fe 3 O 4 Nps On Thementioning
confidence: 93%
“…CK is the soil without earthworm and AM fungi addition; E is the soil with earthworm addition; AM is soil with AM fungi addition; E+AM is the soil with both earthworm and AM fungi addition Data are the means of four replicates±STD and were compared by Duncan's multiple range tests. Within each column (4 values) the values with the same lower case letter are not significantly different CK is the soil without earthworm and AM fungi addition; E is the soil with earthworm addition; AM is soil with AM fungi addition; E+AM is the soil with both earthworm and AM fungi addition AM hyphal Contribution to plant P uptake (%)=(Total P uptake by AM plants-total P uptake by non-AM plants)/Total P uptake by AM plants×100 % (Feng et al, 2003) Utilization efficiency of Ca-P by plants (%) = Total P uptake (mg)/ Total addition Ca-P (50 mg) 2014; Martinez et al 2014), and some of them have been noted as plant growth-promoting rhizobacteria (PGPR) in numerous review articles. Therefore, we think that the effect of earthworms on calcium phosphate bioavailability may be related to 1) production of organic acids by gut microbes and the soil pH decrease, and/or 2) an influence on soil bacterial abundance and increased abundance of Flavobacteriaceae.…”
Section: Impact Of Earthworms On the Bioavailability Of Calcium Phospmentioning
confidence: 99%
“…Earthworm-increased microbial biomass P may be due to the production of organic acids by their gut microbes, which could impact the acid phosphatase biosynthesis in the primary P solubilization of microorganisms (Arcand and Schneider 2006). AM hyphae released exudates, which included organic acids and/or express phosphatase enzymes (e.g., acid/alkaline phosphohydrolases), to regulate the microbial biomass P by stimulating soil microbial activities (Martinez et al 2014). The impact of the interaction between earthworms and AM fungi on the production of organic acids is likely important in microbial turnover during P cycling.…”
Section: Microbial Biomass P With P Cyclingmentioning
confidence: 99%
“…New and emerging methods, such as metagenomics and metaproteomics, which allow for a greater understanding of microbe-metal interactions, many of which were pioneered as a result of academic and U.S. Department of Energy National Laboratory collaborations, have yielded significant insights into subsurface microbial community dynamics and physiological responses within contaminated environments [194][195][196][197][198][199][200][201][202][203][204][205][206]. Additionally, synchrotron X-ray techniques (e.g., XRD, XANES, and EXAFS) have become tools for biogeochemical studies that enhance our understanding of in situ contaminant sequestration.…”
Section: Summary Challenges and Future Directionsmentioning
confidence: 99%